Marked functional improvement after combined chemoradiotherapy for cervical spine glioblastoma causing quadriparesis in an adolescent. (11th February 2014) - Lau, Peter Kar Han; Lee, Gabriel; Bynevelt, Michael; Nowak, Anna K
Abstract : Primary spinal glioblastoma (GBM) is a rare spinal tumour and is considered to have poor prognosis. We describe a case of a 17-year-old adolescent boy with a cervical spine GBM presenting with neck pain and right upper limb weakness. Initial spinal MRI demonstrated a 4.5 cm lesion extending from C2 to C5 suspicious for demyelination. Despite high-dose corticosteroids, his weakness progressed resulting in quadriparesis. Subsequent laminectomy and biopsy confirmed spinal GBM. Shortly after surgery the patient continued to deteriorate and was essentially bedbound. Standard chemoradiotherapy as per the Stupp protocol, together with multimodal rehabilitation, resulted in substantial functional improvement within 6 weeks of initiation. Continued functional improvement was observed for a period of 11 months. Although an Eastern Cooperative Oncology Group (ECOG) performance score of 4 would normally preclude chemoradiotherapy, a prolonged response to treatment and return to independent function were observed.